2006
DOI: 10.1038/sj.jhh.1002099
|View full text |Cite
|
Sign up to set email alerts
|

Body weight and weight change in relation to blood pressure in normotensive men

Abstract: We examined blood pressure (BP) in association with weight change since age 20, body mass index (BMI) at different ages and fat distribution in normotensive individuals using baseline survey data collected in the Shanghai Men's Health Study, an ongoing populationbased prospective cohort study of Chinese men aged 40-74 years. All anthropometric and BP measurements were performed by medical professionals. Included in this analysis were 25 619 men who had no prior history of hypertension, diabetes or cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 42 publications
2
25
0
2
Order By: Relevance
“…To our knowledge, our previous report from the Shanghai Men's Health Study is the first one that has evaluated the association between long-term weight change and prehypertension risk. 19 In that study, blood pressure significantly increased with weight gain among non-hypertensive men. Men who gained 17.2 kg since age 20 (the highest quintile) had a fourfold increased risk of prehypertension compared with those having a weight gain p2 kg (the lowest quintile), which was comparable to the results observed in the present study of non-hypertensive women.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…To our knowledge, our previous report from the Shanghai Men's Health Study is the first one that has evaluated the association between long-term weight change and prehypertension risk. 19 In that study, blood pressure significantly increased with weight gain among non-hypertensive men. Men who gained 17.2 kg since age 20 (the highest quintile) had a fourfold increased risk of prehypertension compared with those having a weight gain p2 kg (the lowest quintile), which was comparable to the results observed in the present study of non-hypertensive women.…”
Section: Discussionmentioning
confidence: 92%
“…A few studies have evaluated long-term weight change in relation to blood pressure, [3][4][5][6][7] focusing primarily on subjects with hypertension or borderline hypertension and largely involving populations with a high prevalence of overweight and obesity. [6][7][8][9][10][11][12][13][14][15][16][17] There is a lack of data on the impact of weight change over time on blood pressure among normotensive individuals, 4,5,17,19 the target population for the primary prevention of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Weight gain was associated with an increased risk of pre-diabetic condition, greater in those who were not overweight in childhood [20]. Many other studies provide data on components of MS among elderly and middle-aged persons in different populations [1,2,21,22,23,24]. Some of our previous research focussed on the life style and nutrition of elderly people [25,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Both are diagnostic entities and are often related to significant weight gain [2,3,4,5]. There are treatment options to optimize glycaemic control also affecting weight gain [6].…”
Section: Introductionmentioning
confidence: 99%
“…Crosssectional and longitudinal epidemiological studies have shown that blood pressure and hypertension are increased significantly with greater body mass index (BMI) and waist circumference (WC) in normal-weight, overweight and obese men and women, and baseline overweight as well as obesity are reported to be an important risk factor for hypertension [1][2][3][4][5][6][7][8][9][10][11][12] . Several longitudinal studies relate hypertension to changes in BMI or adiposity over time [13][14][15][16][17][18][19][20][21][22] . Given the association between long-term weight gain and hypertension risk, cohort studies on the association between baseline obesity and incident hypertension [1][2][3][4][5][6][7][8][9][10][11][12] have a statistical problem because fixed baseline BMI cannot account for any change in BMI during the observation period 23,24) .…”
Section: Introductionmentioning
confidence: 99%